Exploring the Use of ChatGPT in Academic Assignments: Frequency, Benefits, and Perceptions among University Students - Rabiev, Hasan; Sadidan, Ikhwanussafa; Nurhidayah, Novi Anthika Suci (IC-ITECHS, 2024)
The immediate advancement of artificial intelligence has introduced tools like ChatGPT, which are transforming academic practices among university students. This study investigates the frequency of ChatGPT usage, its perceived benefits, and students, views on its impact on academic tasks. Using a mixed- methods approach, the research combines quantitative surveys to assess usage patterns and qualitative interviews for deeper insights. The findings indicates that 71.3% of students primarily use ChatGPT for writing assignments or essays, with 53% rating it as very helpful in improving assignment quality. ChatGPT is valued for enhancing productivity clarifying complex concepts, and refining academic writing. However, concerns regarding over-reliance and ethical issues are prevalent. The study emphasizes the need for guidelines to promote responsible use while maintaining academic integrity. These findings provide important implications for educators and policymakers in integrating AI tools effectively into educational settings.